PERSPEKTIF PEMASARAN: STRATEGI GLOBAL ATAU REGIONAL? - Werner Ria Murhadi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2003)
Although in both economic literatures and practices the most frequently used catchword is